Basal cell adenoma of the parotid gland: Report of a case - MAKINO, Shinya; KAWAI, Tsuyoshi; KAETSU, Atsuo; FUJITA, Katsutoshi; SHIMOZATO, Kazuo; OHIWA, Ichiro; KAMEYAMA, Yoichiro (Japanese Journal of Oral and Maxillofacial Surgery, 1987)
Basal cell adenoma, which belongs to other types of monomorphic adenoma by WHO classification, is a very rare salivary gland tumor. A case of parotid tumor we experienced was a 73 year old female. It was diagnosed adenolymphoma in the first inspection because of its softness and variation in hardness but it also seemed probably to be a mixed tumor during follow-up. Finally it was confirmed as basal cell adenoma.The report of its finding in computed tomography and scintigraphy was presented.